4E analysis and multiobjective optimization of a PEMFC-based CCHP system with dehumidification. (15th November 2021) - Zhao, Junjie; Cai, Shanshan; Huang, Xiaoming; Luo, Xiaobing; Tu, Zhengkai
Abstract: This paper proposes a novel PEMFC-based combined cooling, heating and power (CCHP) system with independent control of refrigeration and dehumidification, which is used in data centers with strict requirements on temperature and humidity. The effects of operating parameters of PEMFC (current density, hydrogen and oxygen pressure) and refrigeration system (hot water distribution ratio, mass flow of cooling water and chilled water) on the 4E (energy, exergy, economy and environment) are investigated. Meanwhile, multiobjective optimization of the above parameters is carried out. The results show that a high inlet pressure is beneficial to improve system efficiency and reduce annual greenhouse gas (GHG) emissions. An increase in the chilled water mass flow increases system efficiency and reduces annual GHG emissions, while an increase in the cooling water mass flow yields the opposite results. Moreover, an increase in the proportion of hot water entering the adsorption chiller causes system efficiency and the annual GHG reduction to initially decrease and then increase. Compared with the unoptimized system, the energy efficiency, exergy efficiency, system cost, GHG emission reduction, electric power, cooling power, heating power and dehumidification rate of the system increase by 5.5%, 0.77%, 10%, 21.27%, 12.87%, 5.37%, 45.73% and 1.53%, respectively.